Random Walk Hypothesis (Rwh) In The Bursa Malaysia Stock Exchange - Ng, Swee Khiang (2005)
The assumptions of the random walk hypothesis (RWH) are tested for Bursa Malaysia Stock Exchange (formerly known as Kuala Lumpur Stock Exchange) indices during the sample period of 1990 to 2005. The entire period is divided into two sub-periods, which are before and after the Asian financial crisis. The findings suggested that the stock price indices did not follow the assumptions of RWH during the entire period. In the sample period before the Asian financial crisis, the behaviour of stock price followed most of the assumptions of RWH. However, in the sample period after the financial crisis, all the assumptions broke down during the economic crisis. In addition, testing for nonlinearity is a rather delicate part in this study and hence, BDS test is employed to investigate the nonlinearity dependencies. The test statistics are very significant which indicated a strong evidence of nonlinearity for post-crisis sub-periods and entire period. However, the result of pre-crisis sub-period from BDS test showed that the IID assumptions were not rejected.